Generation of a Heteropolycyclic and sp3‐Rich Scaffold for Library Synthesis from a Highly Diastereoselective Petasis/Diels–Alder and ROM–RCM Reaction Sequence. Issue 5 (20th December 2018) - Flagstad, Thomas; Azevedo, Carlos M. G.; Troelsen, Nikolaj S.; Min, Geanna K.; Macé, Yohan; Willaume, Anthony; Guilleux, Rachel; Velay, Mélanie; Bonnet, Karine; Morgentin, Remy; Nielsen, Thomas E.; Clausen, Mads H.
Abstract : Efficient access to diverse screening compounds with desirable, lead‐like properties can be a bottleneck in early drug discovery and chemical biology. Herein we present an efficient, rapid route to three structurally distinct classes of compounds (A–C) from a single precursor, which in turn is available through a one‐pot Petasis 3‐component reaction/Diels–Alder cascade reaction. We demonstrate the versatility of the approach through the synthesis of 35 exemplary compounds from the three classes, as well as by the production of 2188 final compounds, which have been included in the Joint European Compound Library of the European Lead Factory. Abstract : An efficient and rapid route to three structurally distinct scaffolds (A–C) from a single precursor which in turn is available through a one‐pot Petasis 3‐component reaction/Diels–Alder cascade reaction. We demonstrate the versatility of the approach through the synthesis of 35 exemplary compounds from the three scaffolds, as well as by the production of 2188 final compounds, which have been included in the Joint European Compound Library of the European Lead Factory.